COT-3 Exosomal microRNA expression signature in blood and cerebrospinal fluid of glioblastoma patients. (6th December 2021) - Yamashita, Daisuke; Suehiro, Satoshi; Ohtsuka, Yoshihiro; Ozaki, Saya; Nishikawa, Masahiro; Inoue, Akihiro; Kohno, Shohei; Ohue, Shiro; Ohnishi, Takanori; Kunieda, Takeharu
Abstract: Analysis of exosomes derived from plasma or cerebrospinal fluid (CSF) has emerged as a promising biomarker platform for therapeutic monitoring in glioblastoma patients. However, the contents of the various subpopulations of exosomes in these clinical specimens remain poorly defined. Here we characterize the relative abundance of miRNA species in exosomes derived from the plasma and CSF of glioblastoma patients. To this end, we first employed miRNA arrays to measure the expression of exosomal miRNAs in the plasma from glioblastoma patients (n = 24) and healthy volunteers (n = 7) as control. In addition, we performed global miRNA profiling of exosomal miRNAs in the CSF from glioblastoma patients (n = 5) and non-tumoral patients (n = 3; hydrocephalus patients) as control. In plasma derived exosomes, 80 miRNAs were altered by >2-fold in glioblastoma patients compared to controls. In CSF, 92 miRNAs were altered by >2-fold in glioblastoma patients compared to controls. Combined analysis of plasma and CSF revealed a similar fold difference in eight miRNAs. Next, we measured these eight miRNAs expression in in the plasma from pre- and post-operative glioblastoma patients (n = 9). Among these eight miRNAs, we identified only one miRNA (miR-34b-3p) that was upregulated in exosomes from pre-operative glioblastoma patients. Our results suggest that miR-34b-3p might have a potential as a novel diagnostic marker or a therapeutic tool for glioblastoma patients.